2021
DOI: 10.1002/pat.5358
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of bioactive aerogel material based on sodium alginate and chitosan for controlled release of levomycetin

Abstract: This work was aimed at obtaining new highly porous two‐component alginate‐chitosan aerogels for use as a controlled‐release drug delivery system. Aerogel materials were prepared on the basis of the sodium alginate–chitosan interpolymer complex using sol–gel and supercritical fluid technologies. The effect of the ratio of sodium alginate and chitosan on the textural characteristics of aerogels and their water uptake capacity was studied. The obtained materials are characterized by a developed mesoporous structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…When the components are combined in a single entity where the individual components remain distinct and separate, the resultant composite material can exhibit different characteristics from the individual components and offer synergistic properties. Hybrid aerogels and their biomedical applications have been recently reported [21,22]. A number of organic-inorganic composite pectin aerogels have been reported, mostly with silica as the second component [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…When the components are combined in a single entity where the individual components remain distinct and separate, the resultant composite material can exhibit different characteristics from the individual components and offer synergistic properties. Hybrid aerogels and their biomedical applications have been recently reported [21,22]. A number of organic-inorganic composite pectin aerogels have been reported, mostly with silica as the second component [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Gorshkova et al produced alginate–chitosan aerogel by combination of sol–gel and supercritical drying technologies. This aerogel demonstrated prolonged levomycetin release rates and has the potential to be employed in a drug delivery application [ 98 ]. Simonson et al investigated a gel-like aerogel in finding the weakness of Mycobacterium tuberculosis (MTB) and tuberculosis (TB)-infected cells to provide correlated pair of peptide and antibiotic for strong and quick antituberculosis treatment.…”
Section: Biomedical Applications Of Aerogelmentioning
confidence: 99%
“…Sodium alginate (SA) is a polysaccharide polymer extracted from brown algae, possessing advantages such as wide availability, low cost, non-toxicity and convenient ion cross-linking. 24 Research on SA-based aerogels has found extensive applications in various fields, including food, medicine and adsorption. However, SA aerogels suffer from drawbacks such as low mechanical strength and structural instability.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, biomass‐based aerogels have gained increasing attention due to their environmental friendliness, non‐toxic nature and absence of secondary pollution. Sodium alginate (SA) is a polysaccharide polymer extracted from brown algae, possessing advantages such as wide availability, low cost, non‐toxicity and convenient ion cross‐linking 24 . Research on SA‐based aerogels has found extensive applications in various fields, including food, medicine and adsorption.…”
Section: Introductionmentioning
confidence: 99%